2018
DOI: 10.1590/0102-311x00009617
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in HAART uptake and differential survival according to exposure category in Rio de Janeiro, Brazil

Abstract: Despite substantial improvement in prognosis and quality of life among people living with HIV/AIDS (PLWHA) in Brazil, inequalities in access to treatment remain. We assessed the impact of these inequalities on survival in Rio de Janeiro over a 12-year period (2000/11). Data were merged from four databases that comprise the national AIDS monitoring system: SINAN-AIDS (Brazilian Information System for Notificable Diseases; AIDS cases), SISCEL (laboratory tests), SICLOM (electronic dispensing system), and SIM (Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Insufficient data to evaluate the time of HIV-1 infection and conventional sequencing usage may have caused an underestimation of TDRM prevalence (Palmer et al, 2005; Jain et al, 2011; Mohamed et al, 2014). Besides, it has been reported that significant inequalities in access to treatment persists in Brazil, resulting in different impacts on mortality in some groups, such as non-white individuals, or those with poor formal education (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient data to evaluate the time of HIV-1 infection and conventional sequencing usage may have caused an underestimation of TDRM prevalence (Palmer et al, 2005; Jain et al, 2011; Mohamed et al, 2014). Besides, it has been reported that significant inequalities in access to treatment persists in Brazil, resulting in different impacts on mortality in some groups, such as non-white individuals, or those with poor formal education (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Free and universal access to ART in Brazil has also provided a significant increase in the quality of life and survival of PLHIV. 13 , 14 Equally important, there was a minimization of economic losses, due to the reduction of morbidity and mortality associated with AIDS, with a consequent decrease in public spending on hospitalizations, high cost and high complexity laboratory and clinical procedures. 14 After all, despite the persistence of inequalities in access to ART in the country, mortality decreased significantly, and the expanded access to ART had a dramatic impact on survival time.…”
Section: Discussionmentioning
confidence: 99%
“…14 After all, despite the persistence of inequalities in access to ART in the country, mortality decreased significantly, and the expanded access to ART had a dramatic impact on survival time. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People living with HIV from a disadvantaged social class are more likely to have a delayed diagnosis, worse access to healthcare, and even worse treatment outcome, which are related to factors such as unemployment, low education, and poor living conditions [ 29 ]. People who inject drugs and other socially disadvantaged and marginalized populations generally suffer late diagnosis and initiate ART in the late stages of infection [ 30 ], compared to MSM who usually initiate ART earlier and are more likely to access HIV-related care, have higher adherence to ART, and experience better treatment outcomes [ 31 ]. Since HIV-acquisition risk has been demonstrated as a primary behavioral factor associated with HIV diagnosis and treatment, the effect of HIV-acquisition risk on uptake of continuous care among people living with HIV receiving ART should be carefully elucidated.…”
Section: Introductionmentioning
confidence: 99%